Quantitative study of the food flavoring spice mixtures used in the traditional markets of District Bannu, Khyber Pakhtunkhwa, Pakistan - Shah, Adnan; Badshah, Lal; W. Bussmann, Rainer; Muhammad, Murad; Abdullah, Abdullah; Ullah, Farman; Khan, Sumbal; Khan, Naushad (Ethnobotany Research and Applications, 2022)
Background: The use of spices is as old as humanity itself, with spice production and trade often having influenced global politics and altering and modeling the very basics of our culture. Methods: This study offers the first documentation of the market value of spice taxa and associated spice recipes, based on interviews and group discussions with 120 participants (12.50% women and 87.50% men), using both semi-structured and open-ended questionnaires. Results: A total of 15 spice mixtures were reported in which 26 spice taxa were used in various proportion, and the prices of each spice taxon were found different in different markets. The highest price per kg was asked for Syzygium aromaticum in Masala Mandi market (PKR 2200, US 14.1), while the lowest price per kg was for Allium cepa in Chuk market (PKR 75, US 0.4). The prices of each one spice mixtures at each market vary from each other. There was a clear-cut difference between the composition and in prices. Laki gate market was the most expensive market where 10 spice mixtures out of 15 had the highest market value. Chuk market was most inexpensive because 11 spice mixtures out of 15 had their lowest market price. The Biryani masala recipe is known to be the heaviest recipe with the highest number of spice taxa (14) followed by Qeema and Machli masala recipes with 11 spice taxa each. Rosh masala was the simplest spices mixture comprising only 5 species out of 26 spice taxa. The market-to-market comparison showed strong correlation between Tanchi and Masala Mandi markets (r = 0.97) and Laki Gate and Masala Mandi markets (r = 0.95). Spice mixtures to spice mixtures correlations showed strong correlation between Kabuli Pulao and Qeema masala recipes (r = 0.99) and Haleem and Garam masala recipes and Achar gosht and Haleem masala recipes (r = 0.98) each. Conclusion: The study highlighted the consistent strong correlation between various markets i.e., Tanchi and Masala Mandi markets and spice mixture to spice mixture e.g., Kabuli Pulao and Qeema masala recipes. The study provides a base line for the sustainable use of recipes, and young researchers. Keywords: Spice taxa, spice mixtures composition, market value, correlation of markets, correlation of spice recipes, Bannu, Pakistan.